REGIONAL SECURITY: THE CURRENT SITUATION AND FUTURE TRENDS IN CENTRAL ASIA - Densmaa, Oyuntsetseg; Baasankhuu Suren (International Journal of Innovative Technologies in Social Science, 2023)
In an interconnected world, the security of a nation is closely intertwined with the security of its neighboring regions. Regional security changes have the potential to significantly impact a nation’s overall security. In the geopolitical and geo-economic scenario, the strategic position and possession of a state or region remains a challenging issue as evident from the evolving strategic scenario of 21st Century international politics. In this framework, the Central Asian region is considered to be of major strategic significance because of its geopolitical position. In addition, the region possesses some of the important energy resources, mainly oil and gas, and access to them is of strategic significance to all involved – regional as well as external players. This study aims to provide an overview of the current situation of Central Asian countries and their prospects in security. Geographically Central Asia, the central part of Asia, this region is directly bordered by influential players in international relations. Central Asia is bordered by the Caspian Sea in the west, China in the east, Afghanistan in the south, and Russia in the north. The region consists of former Soviet republics such as Kazakhstan, Uzbekistan, Tajikistan, Kyrgyzstan, and Turkmenistan. Central Asia has been an area of geopolitical interest due to its strategic location and abundant natural resources. To understand the current situation and future trends in regional security, it is essential to consider a few key factors. First of all, the Political Stability: Central Asia comprises Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan. While these nations have made progress in political stability since gaining independence from the Soviet Union, challenges persist. Authoritarian governance, limited political pluralism, and ethnic tensions have occasionally affected stability in the region. Next, Terrorism and Extremism: Central Asia has faced the threat of terrorism and extremism, primarily from groups like the Islamic Movement of Uzbekistan (IMU), the Taliban, and now the Islamic State (IS). Also, it is Poverty, lack of economic opportunities, and political repression have contributed to the vulnerability of Central Asian populations to radicalization. The intricate balancing act of Central Asian states is examined through the concept of multi-vectors, a strategy used by these nations to diversify foreign alliances and resist domination by any single power.